Looking at the Modern to Better Understand the Ancient: Is It Possible to Differentiate Mars Pigments from Archaeological Ochres? - Maria Cecilia Carangi; Cristina Corti; Laura Rampazzi (Heritage)
This article offers a discussion of the possibility of distinguishing ochres from Mars pigments. The discussion addresses technological, archaeological, and artistic aspects. Natural earth pigments such as ochres, siennas, and umbers have been widely used from the Paleolithic to the present day and still find wide application despite the development of synthetic iron oxide pigment synthesis processes, called Mars pigments. The potential ability of today’s analytical techniques to distinguish between two classes of pigments of the same color with very similar chemical composition—but perhaps sufficient for reliable recognition—is also discussed. The paper begins by addressing the proper use of the terms “ochres” and “Mars pigments” and their accurate identification in artworks. It reviews the literature on the chemical–mineralogical characterization of yellow and red iron pigments and analyzes pigment catalogs to understand how companies distinguish ochres from Mars pigments. An experimental analysis using External Reflection Infrared Spectroscopy (FTIR-ER) compared painting samples made with natural ochres and Mars pigments, confirming the literature findings and suggesting future research directions. Key differences such as hematite in yellow ochres and specific spectral peaks in red ochres support the potential of FTIR-ER spectroscopy as a noninvasive tool for distinguishing pigments, especially for fragile artifacts and archaeological applications.